2021
DOI: 10.1016/j.mcpro.2021.100136
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic Analysis Unveils the HLA Class I-Presented Immunopeptidome in Melanoma and EGFR-Mutant Lung Adenocarcinoma

Abstract: Cancer immunotherapy is ineffective in low TMB EGFRmutant lung adenocarcinoma. Qi et al. performed a comprehensive proteogenomic profiling of HLA class I-presented immunopeptides in high TMB melanoma and low TMB EGFRmutant lung cancer. Similar numbers of immunopeptides were identified from both. Variant, CG antigen, PTM, and lncRNAderived peptides were identified. A novel strategy to identify lncRNA-derived peptides was developed. The direct identification of class I-presented immunopeptides will potentially a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Interestingly, MALAT1 was one of many lncRNAs that we found to encode an antigenic peptide, thus extending the significance of MALAT1 in cancer by connecting its lncRNA expression with a derived peptide and antigen presentation. Whilst we cannot currently comment on the potential immunogenicity of this MALAT1 derived peptide, other studies where bioinformatics approaches have been deployed suggested that tumour associated antigens can be derived from non-canonical parts of the genome although, to our knowledge, this concept remains to be proven [34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, MALAT1 was one of many lncRNAs that we found to encode an antigenic peptide, thus extending the significance of MALAT1 in cancer by connecting its lncRNA expression with a derived peptide and antigen presentation. Whilst we cannot currently comment on the potential immunogenicity of this MALAT1 derived peptide, other studies where bioinformatics approaches have been deployed suggested that tumour associated antigens can be derived from non-canonical parts of the genome although, to our knowledge, this concept remains to be proven [34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 93%
“…The emerging field of proteogenomics has been successfully applied to identify unique HLA-associated mutant peptides in cancer, characterizing HLA-presented epitopes that are expressed specifically by various tumors types (9)(10)(11)(12). Previous work on identifying HBV-HLA epitopes in HCC has been performed, identifying several HBV peptides (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, long-non-coding RNAs (lncRNAs) are especially notable for their crucial role in modulating immune responses [ 15 , 16 ] and their ability to translate short peptides [ 17 ]. LncRNAs have also been reported to translate neoantigens that can be presented by major histocompatibility complex class 1 molecules (MHC I), which contributes to essential cellular immunosurveillance [ 17 ] and expands the range of immunopeptidomes that can be targeted for immunotherapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%